2005
DOI: 10.1080/10473289.2005.10464680
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Biodiesel on Pollutant Emissions of a JP-8–Fueled Turbine Engine

Abstract: The impacts of biodiesel on gaseous and particulate matter (PM) emissions of a JP-8 -fueled T63 engine were investigated. Jet fuel was blended with the soybean oilderived methyl ester biofuel at various concentrations and combusted in the turbine engine. The engine was operated at three power settings, namely ground idle, cruise, and takeoff power, to study the impact of the biodiesel at significantly different pressure and temperature conditions. Particulate emissions were characterized by measuring the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 8 publications
(8 reference statements)
1
25
0
Order By: Relevance
“…This engine has been used to investigate the effect of fuel chemical and physical properties, additives, and engine power setting on gaseous and PM emissions; details on the engine are provided elsewhere (Corporan et al, 2005(Corporan et al, , 2009Wilson et al, 2013). During this effort, the engine was operated at several power Notes: *Not a regulated HAP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This engine has been used to investigate the effect of fuel chemical and physical properties, additives, and engine power setting on gaseous and PM emissions; details on the engine are provided elsewhere (Corporan et al, 2005(Corporan et al, , 2009Wilson et al, 2013). During this effort, the engine was operated at several power Notes: *Not a regulated HAP.…”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts have been performed to sample and quantify HAPs emissions from aircraft engines (Spicer et al, 2009;Spicer et al, 1994;Knighton et al, 2009;Corporan et al, 2005;Kinsey, 2009). The most complete of these methods for measuring a wide range of hydrocarbon species, including low-molecular-weight hydrocarbons (C 1 -C 5 ), aromatics, and unburned fuel constituents, was completed by Spicer (Spicer et al, 2009).…”
Section: Measurement Methodologies For Hapsmentioning
confidence: 99%
“…Hence, the major driver of NO x in gas turbines is the flame temperature which is mainly a concern at full load conditions. Glaude et al 104 in their investigations found a proportional increase in the adiabatic flame temperature with increase in the number carbon atoms in a molecule and the opposite for increase in the H/C ratio. These observations explain the trend observed in the NO x emissions from different fuels in fig 23. Although the GtL/CtL contain a higher H/C ratio and very low aromatic content they produce a higher adiabatic flame temperature compared to FAME with same carbon atoms in the molecule.…”
Section: No Xmentioning
confidence: 96%
“…al. 104 on different blends of biodiesel with JP-8 in a T63 combustor, there was a power output penalty and fuel flow rate had to be increased by 4% to maintain constant output at 20% biodiesel blend due to the lower heat of combustion. Fig 25 shows the relative emissions of particulate matter for different blends of biodiesel at idle, cruise and take-off conditions.…”
Section: Particulate Emissionsmentioning
confidence: 98%
“…The BSPM of biodiesel is 229.8 mg/kWh, on average of the five engine loads, which is 26.5% and 43.3% lower than BSPM of ULSD and LSD, respectively. The effectiveness of biodiesel on reducing particulate emission has been reported in the literature (Corporan et al, 2005;Tsolakis, 2006;Lapuerta et al, 2008). In general, there are three reasons leading to the lower particulate emission with biodiesel.…”
Section: Particle Mass Concentrations and Size Distributionmentioning
confidence: 99%